2006
DOI: 10.2355/isijinternational.46.467
|View full text |Cite
|
Sign up to set email alerts
|

Surface Tension of Liquid Fe–Ti Alloys at 1 823 K

Abstract: Surface tension of liquid Fe-Ti alloys has been determined by using the constrained drop method at 1 823 K in Ar-10%H 2 gas atmosphere. It was found that the surface tension of liquid Fe-Ti alloy decreases slightly with increasing titanium content. In addition, the surface tension of Fe-Ti alloy was also obtained by a theoretical calculation. It was found that the experimental results became slightly lower than the calculated results with increasing titanium content. This paper also discusses the possible reas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…However, there were also a few reports that Ti does not lower the surface tension/contact angle. [14][15][16] The previous observations might be attributed to possible contamination of Ti sample 15) or impurities in alumina substrate used for the contact angle measurement. 17) In particular, Bernhard and co-workers 13,17) found during their contact angle measurement between Fe-Ti alloy and alumina substrate that using almost pure alumina substrate did not lower the contact angle noticeably, while using less pure alumina substrate lowered the contact angle significantly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there were also a few reports that Ti does not lower the surface tension/contact angle. [14][15][16] The previous observations might be attributed to possible contamination of Ti sample 15) or impurities in alumina substrate used for the contact angle measurement. 17) In particular, Bernhard and co-workers 13,17) found during their contact angle measurement between Fe-Ti alloy and alumina substrate that using almost pure alumina substrate did not lower the contact angle noticeably, while using less pure alumina substrate lowered the contact angle significantly.…”
Section: Introductionmentioning
confidence: 99%
“…When observation of nozzle clogging material, 6,8) discrepancies in surface tension/contact angle measurement, [12][13][14][15][16] and oxide stability diagram of the Fe-Al-Ti-O system, [19][20][21][24][25][26][27] it may be suggested that interfacial reaction between liquid Ti-ULC steel and nozzle refractory should be carefully considered. Forming interfacial phase would change adhesion character between the steel and the refractory.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis was performed to identify the mineral composition, Figure 2. The peak intensity observed 2θ=30.29°, 35.49°,43.34°, 53.99°, 57.19°, 62.84°, There observed on crystal plates (220), (311), (400), (422), (511), and (440) confirm the existence of ferrite (cubic spinel) [19] . A bulge of 20 to 30 degrees proved the presence of perlite.…”
Section: Resultsmentioning
confidence: 69%
“…Surface activity of solute relative to iron. 27,30,33,36) 29) indicate the result that the surface tension for liquid Fe-Ti alloy rarely changes in the low Ti concentration range. It has been confirmed that the surface tension for liquid Fe-Cr alloy has no composition dependence based on a measurement result via the levitated oscillating drop method by Nogi et al, 30,31) although the data on the surface tension for liquid Fe-Cr alloy has exhibited a large scatter in the past because of the high reactivity of Cr.…”
Section: Surface Tension For Binary Liquid Fe Alloymentioning
confidence: 99%
“…Although Ce, La and Ti have a high reactivity like Al, no surface tension data have been obtained by the levitated oscillating method for a Fe-based liquid alloy containing Ce, La and Ti. Therefore, the dσ/d[at%] was reviewed based on previous reports28,29) that are not included in Keene's compilation. Ryabov et al28) reported that Ce and La act as a surface active component against liquid steel, which means that Ce and La are considered to be surface active components for liquid iron.…”
mentioning
confidence: 99%